7 important upper body muscles for high performance tennis players - Roetert, E. P.; Ellenbecker, T.; Kovacs, M.; Ochi, S. (Coaching and Sport Science Review, 2024)
This article focuses specifically on the training of key, yet sometimes overlooked by amateur players, muscles and muscle groups that play a major role in both injury prevention and performance enhancement. We can learn from many high performance and professional tennis players and coaches who have adopted these important upper body exercises. The purpose of the selected muscles is to assist in stabilizing a specific joint and additionally allow these joints their proper range of motion. This information is important for players as well as coaches in helping to their players obtain optimal tennis performance. Although many muscles and movement patterns could be addressed, the specific focus of this article is on those often characterized as secondary muscles of the upper body.